2021
DOI: 10.1021/acs.jpclett.1c01123
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of CoTPP Mediated by the Plasmon–Exciton Coupling Effect in the Tunneling Junction

Abstract: CoTPP, as a common hypsoporphyrin, is usually not a luminescent molecule because of the open-shell Co ion. In this paper, well-defined multilayer CoTPP molecules self-assembled on Au(111) surface are characterized layer by layer with scanning tunneling microscope (STM) induced luminescence. By using the highly localized STM tunneling current, we not only investigate the influence of bias polarity on the amplitude of distinct plasmonic emission resulted from the interaction between the metal substrate and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…One of the most important goals in nano-optics is to build nanoscale molecular switches with controlled photon emissions. , Such functional optical devices possess great application potentials in areas ranging from optical data storage/memories to nanoscale light sources. The developments of experimental techniques have made it possible to build actual nanodevices with single molecules as functional units. , Especially, it has been shown that the tunneling electrons in biased metallic junctions such as in a scanning tunneling microscope (STM) could be applied to induce electroluminescence (EL) from single molecules. , These advanced techniques thus opened the door for the design and validation of single-molecule based optical switches at the nanometer scale.…”
mentioning
confidence: 99%
“…One of the most important goals in nano-optics is to build nanoscale molecular switches with controlled photon emissions. , Such functional optical devices possess great application potentials in areas ranging from optical data storage/memories to nanoscale light sources. The developments of experimental techniques have made it possible to build actual nanodevices with single molecules as functional units. , Especially, it has been shown that the tunneling electrons in biased metallic junctions such as in a scanning tunneling microscope (STM) could be applied to induce electroluminescence (EL) from single molecules. , These advanced techniques thus opened the door for the design and validation of single-molecule based optical switches at the nanometer scale.…”
mentioning
confidence: 99%